2007
DOI: 10.1186/1476-7120-5-38
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic incompetence and a higher frequency of myocardial ischemia in exercise echocardiography

Abstract: Background: Exercise echocardiography (EE) is an established method to diagnose coronary artery disease (CAD). Chronotropic incompetence (CI) during the EE may be a marker of myocardial ischemia. The purpose of this investigation was to evaluate the additive value of CI during EE in CAD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…For each increment of three units in the METs, the odds of incompetence is reduced by 66% (p <0.0001). Similar results were found by other studies that confirm the inverse relationship between the presence of incompetence and physical capacity 11,18,20,21,27,28 . In a comparative study among users of pacemaker with fixed ventricular rate and variable rate during exercise, it was observed that the first group, which behaves like HF patients, presented worse tolerance to exertion 29 .…”
Section: -Specificitysupporting
confidence: 80%
See 4 more Smart Citations
“…For each increment of three units in the METs, the odds of incompetence is reduced by 66% (p <0.0001). Similar results were found by other studies that confirm the inverse relationship between the presence of incompetence and physical capacity 11,18,20,21,27,28 . In a comparative study among users of pacemaker with fixed ventricular rate and variable rate during exercise, it was observed that the first group, which behaves like HF patients, presented worse tolerance to exertion 29 .…”
Section: -Specificitysupporting
confidence: 80%
“…Moreover, it is confirmed to present diagnostic accuracy superior to that of the ET, especially in patients with HF 11 .…”
mentioning
confidence: 61%
See 3 more Smart Citations